2007
DOI: 10.1038/ng2056
|View full text |Cite
|
Sign up to set email alerts
|

A conserved microRNA module exerts homeotic control over Petunia hybrida and Antirrhinum majus floral organ identity

Abstract: It is commonly thought that deep phylogenetic conservation of plant microRNAs (miRNAs) and their targets 1,2 indicates conserved regulatory functions. We show that the blind (bl) mutant of Petunia hybrida 3 and the fistulata (fis) mutant of Antirrhinum majus 4,5 , which have similar homeotic phenotypes, are recessive alleles of two homologous miRNA-encoding genes. The BL and FIS genes control the spatial restriction of homeotic class C genes 6,7 to the inner floral whorls, but their ubiquitous early floral exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 32 publications
4
123
0
2
Order By: Relevance
“…In se-1 and ago1-27 mutants as well as Pro35S:MIM156 plants, all of which have reduced miR156 activity, we observed a clear increase in the levels of the SPL9 target mRNA but no obvious expansion of its expression domain. Thus, miR156 appears to be at the other end of possibilities for miRNA target interactions, with its main role being quantitative control of target mRNA levels, similar to what has been reported for miR169 and its targets in snapdragon (Antirrhinum majus) and petunia (Petunia hybrida; Cartolano et al, 2007). This conclusion is supported by a comparison of SPL9 and miR156 expression patterns, which strongly overlap (Figure 3).…”
Section: Regulation Of Spl Expression By Mir156supporting
confidence: 79%
“…In se-1 and ago1-27 mutants as well as Pro35S:MIM156 plants, all of which have reduced miR156 activity, we observed a clear increase in the levels of the SPL9 target mRNA but no obvious expansion of its expression domain. Thus, miR156 appears to be at the other end of possibilities for miRNA target interactions, with its main role being quantitative control of target mRNA levels, similar to what has been reported for miR169 and its targets in snapdragon (Antirrhinum majus) and petunia (Petunia hybrida; Cartolano et al, 2007). This conclusion is supported by a comparison of SPL9 and miR156 expression patterns, which strongly overlap (Figure 3).…”
Section: Regulation Of Spl Expression By Mir156supporting
confidence: 79%
“…Recently, with the completion of several genome and EST projects, the amount of sequence data has increased drastically and allowed the effective use of mutant populations to investigate gene function in high-throughput reverse genetic approaches (Alonso and Ecker, 2006). In petunia, gene function studies have profited from the endogenous system of transposable elements (van den Broeck et al, 1998) to characterize the genetic determinants of a wide range of biological processes (Baumann et al, 2007;Cartolano et al, 2007;Simons et al, 2007). Although highly effective, transposon tagging employing non-engineered sequences can only generate loss-of-function mutations and the unstable nature of the insertion may impair long-term genetic analyses (Alonso and Ecker, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to date, no A-function could be attributed to petunia orthologs of the Arabidopsis A-function genes. Instead, we found that in both petunia and snapdragon one aspect of the A-function, restriction of C-class activity to stamens and carpels, is encoded by a microRNA, named BLIND in petunia and FISTULATA in snapdragon (Antirrhinum majus; Cartolano et al, 2007).…”
Section: Introductionmentioning
confidence: 91%